Performance Simulation of a Horizontal Shell Tube Evaporator using EES (Damascus University Journal for engineering sciences, 2021)
A performance simulation study has been conducted for a shell tube evaporator for different refrigerants (R-22,R-134a,R-12,Ammonia), where  EES software has been used in order to investigate of the effect of changing different design parameters (Heat Load, Temperature Difference between Inlet and Outlet for the saline solution, Heat Resistance for Tubes, Velocity of the saline solution) on the geometrical parameters of the evaporator (Heat Exchange Total Area, Total Number of Tubes). The study showed that the use of Ammonia as a refrigerant would decrease the total number of tubes and decrease the total cost of the evaporator.
Keywords: Heat Load; Total Number of Tubes; Saline Solution Velocity; Nusselt Number; Heat Resistance of Tubes.